DNA barcoding of perennial fruit tree species of agronomic interest in the genus Annona (Annonaceae) - Larranaga, Nerea; Hormaza, Jose I. (Frontiers in Plant Science, 2015)
The DNA barcode initiative aims to establish a universal protocol using short genetic sequences to discriminate among animal and plant species. Although many markers have been proposed to become the barcode of plants, the Consortium for the Barcode of Life (CBOL) Plant Working Group recommended using as a core the combination of two portions of plastid coding region, rbcL and matK. In this paper, specific markers based on matK sequences were developed for 7 closely related Annona species of agronomic interest (Annona cherimola, A. reticulata, A. squamosa, A. muricata, A. macroprophyllata, A. glabra and A. purpurea) and the discrimination power of both rbcL and matK was tested using also sequences of the genus Annona available in the Barcode of Life Database (BOLD) data systems. The specific sequences developed allowed the discrimination among all those species tested. Moreover, the primers generated were validated in six additional species of the genus (A. liebmanniana, A. longiflora, A. montana, A. senegalensis, A. emarginata and A. neosalicifolia) and in an interspecific hybrid (A. cherimola x A. squamosa). The development of a fast, reliable and economic approach for species identification in these underutilized subtropical fruit crops in a very initial state of domestication is of great importance in order to optimize genetic resource management.